A Reflection of the Author's Life in Anne Rice's Novel Interview with the Vampire - Mery; Kinasih, Putri Rindu (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2024)
Interview With The Vampire is the first novel in Anne Rice’s vampire chronicles series, which was published in 1976. Interview with the Vampire has been nominated for various awards since its initial release in 1976, including the Bram Stoker Awards and the British Fantasy Awards. Unfortunately, many people are unaware that Rice’s firsthand experiences inspiring this novel. Previous research had managed to highlight the relationship between the author’s life with her literature works but none of them were related to vampire stories. Even though people might find monsters’ story is implausible, readers and viewers of fantasy, science fiction, and horror have the desire to explore the impossible (Athans, 2014). In addition, Wood (1999) strongly added that the details Rice has made about vampire has entirely changed the general vampire world. Rice’s major changes are: vampires were made more reasonable, believable, sympathetic, modern, and suited to the urban setting. On top of that, Rice has put the vampire closer to the readers as the story was told in first-person narration. Considering all of these, the researchers were intrigued in analyzing further the portrayal of Rice’s biography in her novel. This research used the descriptive qualitative method. While data in this research were taken from the novel Interview with the Vampire. This study found a resemblance of Anne Rice’s adulthood stage of life in Louis’s life. In addition, it is also found out that there are similarities between the characters in the novel with the real family member of Anne Rice and her childhood environment. Finally, the study was carried out by conducting a biographical study. The resemblances of characters with people of her life, Rice persuaded the readers to not only like and empathize with vampires, but also to trust them. Keywords: Literature, biographical analysis, novel, vampire.